OPTIMALISASI MOTIVASI DAN KEDISIPLINAN KERJA PADA BURUH DI PT. DUTA NUSA LESTARI KABUPATEN KAPUAS HULU - Daniel, Daniel; Maswadi, Maswadi; Parulian Hutajulu, Josua (Fakultas Pertanian Universitas Janabadra, 2025)
Palm oil companies are increasing in number from year to year. If the company does not have good employee performance, it will be difficult to compete with other companies. The achievement of a company's goals cannot be separated from the importance of employee performance, including workers. Workers at PT. Duta Nusa Lestari, Kapuas Hulu Regency, do not yet have effective performance, this is influenced by low motivation and work discipline in workers. The purpose of this study is to analyze aspects of motivation and work discipline to improve worker performance at PT. Duta Nusa Lestari, Kapuas Hulu Regency. This study uses a descriptive quantitative method and data analysis with AHP (Analytical Hierarchy Process) Expert Choice 11 software. This study used 43 samples taken by purposive sampling. The results of this study state that the optimal main priority for improving worker performance from the motivation criteria is physiological needs with a weight of 0.564 and the main priority from the discipline criteria is to do work according to SOP with a weight of 0.345. The alternative to prioritized motivation is a salary that meets needs with a weight of 0.202 and the alternative to prioritized discipline is responsibility for the task being carried out with a weight of 0.243.